2016
DOI: 10.1039/c6cc01564f
|View full text |Cite
|
Sign up to set email alerts
|

Glycomimetic-based pharmacological chaperones for lysosomal storage disorders: lessons from Gaucher, GM1-gangliosidosis and Fabry diseases

Abstract: Lysosomal storage disorders (LSDs) are often caused by mutations that destabilize native folding and impair the trafficking of enzymes, leading to premature endoplasmic reticulum (ER)-associated degradation, deficiencies of specific hydrolytic functions and aberrant storage of metabolites in the lysosomes. Enzyme replacement therapy (ERT) and substrate reduction therapy (SRT) are available for a few of these conditions, but most remain orphan. A main difficulty is that virtually all LSDs involve neurological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 174 publications
(147 reference statements)
1
117
0
1
Order By: Relevance
“…The finding that PGRN acts as a co-chaperone of HSP70 and is required for disaggregation of GCase, together with the facts that chaperone-based treatments aiming to enhance GCase lysosomal localization have proven to be a promising alternative to enzyme replacement treatment (ERT) and substrate reduction therapy (SRT) for GD (Zimran et al, 2013, Sanchez-Fernandez et al, 2016, Jung et al, 2016, Mena-Barragan et al, 2015), and recombinant HSP70 has been shown to effectively correct altered lysosomal stability seen in Niemann–Pick B disease (NPD) (Kirkegaard et al, 2010), promoted us to examine whether PGRN would have therapeutic effects in GD. Indeed, we have found that recombinant PGRN protein is therapeutic against Gaucher disease (Jian et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that PGRN acts as a co-chaperone of HSP70 and is required for disaggregation of GCase, together with the facts that chaperone-based treatments aiming to enhance GCase lysosomal localization have proven to be a promising alternative to enzyme replacement treatment (ERT) and substrate reduction therapy (SRT) for GD (Zimran et al, 2013, Sanchez-Fernandez et al, 2016, Jung et al, 2016, Mena-Barragan et al, 2015), and recombinant HSP70 has been shown to effectively correct altered lysosomal stability seen in Niemann–Pick B disease (NPD) (Kirkegaard et al, 2010), promoted us to examine whether PGRN would have therapeutic effects in GD. Indeed, we have found that recombinant PGRN protein is therapeutic against Gaucher disease (Jian et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, ERT has the disadvantage of being expensive; in addition, it does not impact neurological symptoms due to its inability to cross the blood–brain barrier due to its size. Therefore, screening for smaller compounds or developing them though design is a promising approach, and a number of compounds with various chemistries have been developed [103,104]. Some of these compounds have chaperone activity and increase levels of active GCase by enhancing correct folding during trafficking to the lysosome, but others may act though alternative mechanisms.…”
Section: Drug Discovery Using Ipsc Modelsmentioning
confidence: 99%
“…В настоящее время развиваются новые терапевтиче-ские направления -лечение белками-шаперонами и ген-ная терапия [126][127][128][129][130][131][132][133][134]. Также проводятся исследования комбинации сапосина В с модифицированной α-N-ацетил-галактозаминидазой [135].…”
Section: примеры ангиокератомы у мужчин с «классической» болезнью фабриunclassified